A complete system modelling of piezoelectric energy harvester (PEH) with silicon carbide (SiC) used as cantilever base - Mohd Noor Fakhzan, Mohd Kazim (Penerbit UTM Press, 2015)
Link to publisher's homepage at http://www.penerbit.utm.my/